Risk of Thromboembolic Events in Cancer Patients Treated with Immune Checkpoint Inhibitors: A Meta-analysis of Randomized Controlled Trials - Ma, Zhuo; Sun, Ximu; Zhang, Yi; Li, Hao; Sun, Dan; An, Zhuoling; Zhang, Yuhui (Thrombosis and Haemostasis, 2022)
Background The association between immune checkpoint inhibitors (ICIs) and thromboembolic events (TEEs) remains controversial.Objective The goal of this study was to assess the risk of major TEEs associated with ICIs.Methods We explored ICI-related TEEs in randomized controlled trials available in ClinicalTrials.gov and electronic databases up to June 30, 2021. Meta-analysis was performed by using Peto odds ratios (ORs) with 95% confidence intervals (CIs).Results A total of 61 studies were included. Patients treated with ICIs had a similar risk of venous thromboembolism (VTE) but a significantly increased risk of arterial thromboembolism (ATE) (Peto OR: 1.58 [95% CI: 1.21–2.06]) compared with non-ICI regimens. Stratified by different regimens, only PD-L1 (programmed cell death ligand 1) inhibitors showed a significant increase in ATE (Peto OR: 2.07 [95% CI: 1.26–3.38]). The incidence of VTE was higher in PD-1/PD-L1 inhibitor and CTLA-4 (cytotoxic T lymphocyte antigen 4) inhibitor combination therapies compared with monotherapies (Peto OR: 2.23 [95% CI: 1.47–3.37]). Stratified by tumor, for pulmonary embolism (PE) and cerebral ATE, the statistically significant results were only seen in lung cancer patients (Peto OR: 1.42 [95% CI: 1.02–1.97]; Peto OR: 2.10 [1.07–4.12]), and for myocardial infarction, the statistically significant result was only seen in other tumor types (Peto OR: 2.66 [95% CI: 1.68–4.20], p < 0.0001).Conclusion There was no significant increase in the overall risk of VTE in patients treated with ICIs; however, special attention should be given to the risk of VTE in PD-1/PD-L1 inhibitor and CTLA-4 inhibitor combination therapy and PE in lung cancer patients. PD-L1 inhibitors were associated with a significant increase in ATE.
Keywords: immune checkpoint inhibitors; thromboembolic events; cancer; VTE events; ATE events